Pharmaceutical assistance to patients with Systemic Lupus Erythematosus under Azthioprine and Hydroxychloroquine: a literature review (Research, Society and Development, 2022)
The present study aims to report the importance of pharmaceutical care for patients with Systemic Lupus Erythematosus using Azathioprine and hydroxychloroquine. And specifically, describe the role of Pharmaceutical Care for patients with chronic diseases; present the characteristics of the autoimmune disease Lupus erythematosus; and demonstrate the need for pharmacotherapeutic monitoring of the drugs Azathioprine and Hydroxychloroquine. This study was carried out through a bibliographic and systematic review and online data collection. As for the use of Azathioprine, it is considered one of the safest when it comes, mainly, to more severe clinical conditions related to lupus nephritis. With regard to Hydroxychloroquine, in its use for the treatment of SLE, the drug is responsible for acting by inhibiting the B cell receptor and signaling. In this sense, the drug treatment of SLE must occur in a strategic and individualized way for each case, since it will depend on which organs were affected and the severity of the symptoms, since the analysis of intervention in the health-disease process carried out by the pharmacist, must have information regarding the symptoms presented by the patient: the beginning of the problem, the duration, the severity, the description, if it is acute or chronic, if it has concomitant symptoms, if it has aggravating or relieving factors, and the presence or not from previous treatments. Therefore, pharmaceutical care serves as a way to control the use of medicines, so that the effect of the medication is effective and effective, without causing damage to human life.